Learning from Results-Based Management evaluations and reviews - and Vähämäki, Janet; Verger, Chantal (OECD, 2019)
What have we learned from implementing results-based management in development co-operation organisations? What progress and benefits can be seen? What are the main challenges and unintended consequences? Are there good practices to address these challenges? To respond to these questions this paper reviews and analyses the findings from various evaluations and reviews of results-based management systems conducted by members of the Development Assistance Committee (DAC), the OECD/DAC Results Community Secretariat and other bodies in the past four years (2015-2018). It also draws on emerging lessons from new methods for managing development co-operation results. This analytical work aims to: identify recent trends in results-based management, explore challenges faced by providers when developing their results approaches and systems, select good practices in responding to these challenges that can be useful for the OECD/DACResults Community, considering new approaches, new technologies and evolving contexts. This body of evidence will inform the development of a core set of generic guiding principles for results-based management in development co-operation.